In situ Sub‐Cellular Identification of Functional Amyloids in Bacteria and Archaea by Infrared Nanospectroscopy. Issue 6 (6th May 2021) - Otzen, Daniel E.; Dueholm, Morten S.; Najarzadeh, Zahra; Knowles, Tuomas P. J.; Ruggeri, Francesco Simone
Abstract: Formation of amyloid structures is originally linked to human disease. However, amyloid materials are found extensively in the animal and bacterial world where they stabilize intra‐ and extra‐cellular environments like biofilms or cell envelopes. To date, functional amyloids have largely been studied using optical microscopy techniques in vivo, or after removal from their biological context for higher‐resolution studies in vitro. Furthermore, conventional microscopies only indirectly identify amyloids based on morphology or unspecific amyloid dyes. Here, the high chemical and spatial (≈20 nm) resolution of Infrared Nanospectroscopy (AFM‐IR) to investigate functional amyloid from Escherichia coli (curli), Pseudomonas (Fap), and the Archaea Methanosaeta (MspA) in situ is exploited. It is demonstrated that AFM‐IR identifies amyloid protein within single intact cells through their cross β‐sheet secondary structure, which has a unique spectroscopic signature in the amide I band of protein. Using this approach, nanoscale‐resolved chemical images and spectra of purified curli and Methanosaeta cell wall sheaths are provided. The results highlight significant differences in secondary structure between E. coli cells with and without curli. Taken together, these results suggest that AFM‐IR is a new and powerful label‐free tool for in situ investigations of the biophysical state of functional amyloid and biomolecules in general. Abstract : To overcome the limited spatial resolution of conventional bulk and spectroscopic approaches, here, the high sensitivity and spatial resolution of infrared nanospectroscopy to investigate the secondary and quaternary structure of functional amyloids in situ at the sub‐cellular scale within E. coli, Pseudomonas, and Methanosaeta cells is applied.